2012
DOI: 10.1021/la300611g
|View full text |Cite
|
Sign up to set email alerts
|

Facile Method for the Fabrication of Robust Polyelectrolyte Multilayers by Post-Photo-Cross-Linking of Azido Groups

Abstract: In this letter, we have developed a facile method to enhance the stability of polyelectrolyte multilayers. We fabricate conventional polyelectrolyte multilayers of PAH/PAA through electrostatic layer-by-layer (LbL) assembly and then postinfiltrate photosensitive cross-linking agent 4,4'-diazostilbene-2,2'-disulfonic acid disodium salt into the LbL films. After cross-linking by UV irradiation, the stability of the photo-cross-linked multilayer is highly improved as evidenced by the lack of dissolution under ult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 55 publications
(53 citation statements)
references
References 45 publications
(25 reference statements)
3
48
2
Order By: Relevance
“…The inltration of DAS into the multilayers was monitored using the UV-vis spectra using its characteristic absorbance at 340 nm ( Fig. [37][38][39][40] The kinetics of the reaction are shown in Fig. The amount of the absorbed DAS per bilayer was estimated as 0.71 mg cm À2 using our previously reported calculation method.…”
Section: Resultsmentioning
confidence: 99%
“…The inltration of DAS into the multilayers was monitored using the UV-vis spectra using its characteristic absorbance at 340 nm ( Fig. [37][38][39][40] The kinetics of the reaction are shown in Fig. The amount of the absorbed DAS per bilayer was estimated as 0.71 mg cm À2 using our previously reported calculation method.…”
Section: Resultsmentioning
confidence: 99%
“…[21][22][23] In this study, the decomposition of DAS was evident by the decrease of the absorbance to around 340 nm (Fig. Previous studies have shown that upon UV irradiation, the photo-active DAS decomposes into nitrene species and forms covalent linkages with adjacent C-H, O-H, and N-H functional groups.…”
Section: Resultsmentioning
confidence: 85%
“…Here, we employed DAS as the photosensitive crosslinking agent as it is a bifunctional photoactive molecule, carrying two sulfonic groups and two azido groups in the molecular structure, which bring the following important functions: first, due to the existence of sulfonic groups, DAS is endowed with good water solubility and is negatively charged, hence it can easily infiltrate and diffuse into the multilayers containing positively charged PAH driven by the electrostatic attraction. Second, the two azido groups located at the two ends of DAS structure are key factors, because they are able to generate two nitrene groups with extremely high reactivity under UV irradiation, which are expected to insert into the adjacent C(sp 3 )-H, C(sp 2 )-H, N-H bonds non-selectively, forming interlayer cross-linking covalent bonds(Scheme 2) [35] . Based on the above considerations, we first immersed the as-assembled PAH/PVS multilayers substrate in an aqueous solution of DAS(5 mg/mL, pH=3.8) and researched the adsorption kinetics of DAS with UV-Vis spectroscopy measurements, as shown in Fig.3.…”
Section: Constructing Inter-layer Covalent Bonds Through Post-photochmentioning
confidence: 99%
“…While in the case of azido groups, the synthesis of special compounds grafted with phenyl azido groups, in advance, is still required. Based on the above analysis, a new and improved method of directly introducing a difunctional photoactive molecule as a cross-linking agent was developed, in order to expand the applications of the multilayers and simplify the reaction operation in the photochemical cross-linking reaction strategy [35] . Currently, there are a few reports on the successful application of combining post-infiltration of difunctional molecules with photochemical cross-linking reactions to stabilize LbL assembled films [36,37] .…”
Section: Introductionmentioning
confidence: 99%